(untitled) (Global Journal of Human-Social Science, 2014)
This paper is primarily concerned to explore wide-range of socio-economic and political dimensions of marginalization that characterizes Ayille minority group in Woliatta zone, Southern Ethiopia. It investigates the overall living condition of Ayilles in terms of economic, social and political aspects within the socio-cultural endeavors of the host society. The study has been carried out in three purposely identified areas in Woliatta zone. Across sectional qualitative method was employed (in-depth interview and Focus Group Discussion) involving a total of 37 in-depth informants, 6 Focus group discussions comprising of 6 individuals in each group through purposive and snowball sampling techniques. Traditionally, this group lost the rights and privileges in the society at large and did not get equal treatment similar to other people. In the years before 1974 revolution, some of them did not own essential resources like land and livestock of any kind. They were restricted in social interaction and prohibited from participating in social activities collectively with the dominant groups. However, after 1974 revolution the living condition of Ayilles generally improved since they gained access to land. Accompanied with this, the social relationship they had with the host society enhanced.